Snow loads : guide to the snow load provisions of ASCE 7-10 - O'Rourke, Michael J. (ASCE Press, 2010)
This book provides detailed authoritative description of the snow load provisions of ASCE/SEI Standard 7-10. With clear, concise language, the book illustrates the key concepts and guides users in applying the provisions in the design of new and existing structures that are subject to falling or drifting snow. Like its predecessors that accompanied earlier editions of the Standard, this new book includes examples of flat roof loads, sloped roof loads, partial loads, and all types of conventional drift loading. New material includes design examples for leeward drift and sliding loads on adjacent structures and an improved discussion of bays susceptible to ponding loads. The Frequently Asked Questions chapter has been expanded and now covers six additional questions. This is an essential supplement to ASCE/SEI Standard 7 for all engineers, architects, and construction professionals who work on projects in regions subject to snow. --